'Social Distancing' and Hierarchies of Belonging: The Case of Displaced Population from Donbas and Crimea. Issue 3 (15th March 2020) - Sereda, Viktoriya
Abstract: Following the 2013–2014 protests against then Ukrainian president Viktor Yanukovych, Russia's annexation of Crimea and the armed conflict in Donbas, one of the major challenges for Ukrainian society has been the displacement of over two million of its inhabitants. In 2015, at the peak of the displacement, Ukraine found itself among the five countries in the world, after Yemen, Syria, Iraq and Nigeria, with the highest number of internally displaced persons (IDPs) associated with conflict and violence, and it continues to rank highest in Europe. Very little research has been done to provide a detailed analysis of how internally displaced persons living in Ukraine and outside the country claim and negotiate their belonging in the aftermath of the Revolution of Dignity and the ensuing war. Feeling of belonging is constructed through a relational process of self- and external categorisation and depends on acknowledgement by other members of the chosen group, therefore this essay also examines the strength and regional specificity of the social distancing towards different groups of Ukrainian IDPs.